Network outages – pick your battles. (December 2015) - Adato, Leon
Abstract : Network and security incidents can offer valuable lessons for the future, but not if you invest too much money, time and resources into examining something that could never have been foreseen. With events that happen very rarely, spending more than the cost incurred by the event itself in order to prepare for it happening again may be a waste. Measured against that are instances in which, with proper monitoring in place, minor faults in network systems can be fixed cheaply and result in large cost savings. It's a matter of knowing what's important to your business, explains Leon Adato of SolarWinds. Success isn't achieved as a result of waking up one day with all the answers. Rather it's a slow process of trial and error, innovative thinking and learning from one's mistakes. In fact, the school of hard knocks is the alma mater of some of the world's most successful business people – and the same is no less true for IT pros.